Inovasi muamalah di era modern: jual beli online dan perpustakaan digital - Mukharomah, Awwalina (Maliki Interdisciplinary Journal, 2025)
Nowadays, innovation is something that is no longer foreign, innovation or renewal is needed in an era that also experiences many changes and renewals, including in the aspect of muamalah. The emergence of the phenomenon of online buying and selling and online lending of goods is an innovation that is no longer foreign to find. This innovation ultimately raises new questions regarding its legal review in Islam considering its new nature and there is no evidence that explicitly explains the two innovations. Based on the research that has been conducted, the results obtained are that these innovations are halal and permissible to be carried out, considering that both were created for the benefit of the community by relying on the principle "the original law in muamalah is permissible as long as there is no evidence that prohibits it".